PERAN ASEAN INTERGOVERNMENTAL COMMISSION ON HUMAN RIGHTS (AICHR) DALAM MENANGANI KASUS PELANGGARAN HAK ASASI MANUSIA ROHINGYA-MYANMAR 2012-2016 - Aldian Saputra; Muhammad Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This reseacrh analyzes the role of the ASEAN Intergovernmenal Commission on Human Rights (AICHR) in Handling Cases of Human Rights Violations of Rohingya-Myanmar in 2012-2016. More than a year from the set limit, Rohingya refugees are still mostly in shelters in Indonesia and Malaysia. Myanmar's reluctance to recognize the Rohingya as citizens has made repatriation difficult. Meanwhile, the condition of sectarian tension in Myanmar was still going on in the Rakhine State and the Rohingyas have been victims of this conflict so that hundreds of thousands of Rohingya people have returned to their homes. Together with Malaysia, Indonesia will only temporarily accommodate refugees who were adrift at sea with a total of approximately 7000 people. The temporary shelter was carried out for a maximum of one year and during that time the two countries do not want to accept new refugees from outside with a predetermined number. This research uses qualitative methods by collecting data from books, academic journals, official documents, and also sources from the internet related to research issues regarding the Role of the ASEAN Intergovernmental Commission on Human Rights (AICHR) in Handling Cases of Human Rights Violations of Rohingya-Myanmar 2012- 2016. This research uses the Pluralism Perspective and the level of group analysis. While the theory used in this research was the theory of International Organization and uses the concept of Human Rights. This research finds that humanitarian aid has been widely channeled to the Rohingya by the AICHR countries that have hosted them. Although there are still limitations and obstacles experienced by AICHR in upholding regional human rights, especially in Myanmar, as an international organization AICHR has made efforts to realize the common goal of protecting human rights and creating a peaceful region. Keywords: AICHR, HAM, Rohingya, Myanmar, Etnis